Master your next move : the essential companion to The first 90 days - Watkins, Michael, 1956- (Harvard Business Press, 2019)
Your next professional move can make or break your career--are you ready? In business, especially today, you are only as successful as your next career transition. Do well, and you'll be on the fast track to even more challenging roles. Fail, and you could irreparably harm your career--and your organization. In his international bestseller The First 90 Days, transition guru Michael D. Watkins outlined a set of common principles for getting up to speed quickly in new professional roles. Since that book was published, Watkins has worked with thousands of leaders helping them to accelerate their transitions. These leaders posed challenging questions on how to apply the basic principles in real-life situations. The truth that emerged: The First 90 Days framework can be applied in every transition, but the way you apply it is entirely different when you have been promoted to a higher level than it is when you are joining a new organization, or taking a role in a different country. Master Your Next Move answers this distinct need, focusing on the most common types of transitions leaders face and the unique challenges posed by each. Based on years of research, and now with a new introduction, this indispensable book explores eight crucial transitions virtually everyone faces during their career, including promotion, leading former peers, onboarding into a new company, making an international move, and turning around a business in crisis. With real-world examples and lots of practical models and tools, Master Your Next Move is your guide to surviving and thriving as you make your next move...and every one after that.--